Confinement, an e-learning booster: Changes study in content e-learning consumption and causality analysis trough a Bayesian Network - Carrero Márquez, Oliver; Marín Palacios, Cristina; Botey Fullat, María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The confinement has been one of the measures adopted to mitigate the effects of Covid-19 with the greatest effect on society, such as changes in the consumption of content e-learning due to their need to acquire new knowledge. The objective is to establish causal links between periods of confinement and the growth of consumption of e-learning resources. Data on the use of a e-learning channel have been taken and Bayesian Network have been used as a methodological instrument. The results confirm this causal relationship. It shows lines of cause-effect research that could improve e-learning content attending on the user behavior.